2010
DOI: 10.3324/haematol.2009.016758
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic cystitis after allogeneic hematopoietic stem cell transplants is the complex result of BK virus infection, preparative regimen intensity and donor type

Abstract: BackgroundHemorrhagic cystitis is a common cause of morbidity after allogeneic stem cell transplantation, frequently associated with BK virus infection. We hypothesized that patients with positive BK viruria before unrelated or mismatched related donor allogeneic hematopoietic stem cell transplantation have a higher incidence of hemorrhagic cystitis. Design and MethodsTo test this hypothesis, we prospectively studied 209 patients (median age 49 years, range 19-71) with hematologic malignancies who received bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
71
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(81 citation statements)
references
References 21 publications
(37 reference statements)
5
71
2
3
Order By: Relevance
“…Hemorrhagic cystitis (HC) may occur after HSCT either as early-onset disease due to conditioning toxicity, or late-onset disease associated with GVHD or viral infections such as BK virus, adenovirus, and cytomegalovirus (CMV) [4,5,6,7,8,9]. The incidence of HC after HSCT has been reported to range from 10 to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhagic cystitis (HC) may occur after HSCT either as early-onset disease due to conditioning toxicity, or late-onset disease associated with GVHD or viral infections such as BK virus, adenovirus, and cytomegalovirus (CMV) [4,5,6,7,8,9]. The incidence of HC after HSCT has been reported to range from 10 to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Given the timing of its occurrence, HC can be divided into early onset (occurring within a few days after transplantation) and late onset (LO; occurring weeks later) subtypes, each with distinct pathogenetic factors. Early-onset HC mainly results from uroepithelial injury induced by chemotherapy/irradiation during conditioning, while LO-HC is frequently associated with viral infection and ongoing acute graft-versus-host disease (GVHD) [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhagic cystitis is commonly associated with BK infection, occurring in 10% to 25% of recipients [8,15], although a direct correlation for BK viruria and hemorrhagic cystitis has not been established. In fact, in a multivariate analysis for predictors of hemorrhagic cystitis in patients receiving HCT at M. D. Anderson, the presence of BK viruria was not found to be a significant factor [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Development of BK viruria and associated nephropathies, including hemorrhagic cystitis, is dependent on several factors including type of conditioning regimen, use of T cell-depleted grafts, and use of related or unrelated donor grafts [17,18]. Leung et al suggested 3 phases for the development of BK virus hemorrhagic cystitis [19].…”
Section: Introductionmentioning
confidence: 99%